Previously undetected human hematopoietic cell populations with short-term repopulating activity selectively engraft NOD/SCID-β2 microglobulin–null mice - Glimm, H. (American Society for Clinical Investigation, 2001)
Increasing use of purified or cultured human hematopoietic cells as transplants has revealed an urgent need for better methods to predict the speed and durability of their engraftment potential. We now show that NOD/SCID-β2 microglobulin–null (NOD/SCID-β2m(–/–)) mice are sequentially engrafted by two distinct and previously unrecognized populations of transplantable human short-term repopulating hematopoietic cells (STRCs), neither of which efficiently engraft NOD/SCID mice. One is predominantly CD34(+)CD38(+) and is myeloid-restricted; the other is predominantly CD34(+)CD38(–) and has broader lymphomyeloid differentiation potential. In contrast, the long-term repopulating human cells that generate lymphoid and myeloid progeny in NOD/SCID mice engraft and self-renew in NOD/SCID-β2m(–/–) mice equally efficiently. In short-term expansion cultures of adult bone marrow cells, myeloid-restricted STRCs were preferentially amplified (greater than tenfold) and, interestingly, both types of STRC were found to be selectively elevated in mobilized peripheral blood harvests. These results suggest an enhanced sensitivity of STRCs to natural killer cell–mediated rejection. They also provide new in vivo assays for different types of human STRC that may help to predict the engraftment potential of clinical transplants and facilitate future investigation of early stages of human hematopoietic stem cell differentiation.